Code Switching Found In Meats Theme Video Of Korea Reomit Youtube Channel - Desi Rohma Khurniawati; Ratini Setyowati; Aris Hidayatulloh (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
The importance of English in Indonesia has grown significantly in recent years. This widespread influence is obvious in various sector of Indonesia seciety, from business to education and media. Digital platforms like YouTube play a significant role in English language learning by exposing young Indonesians to English content and bilingual speakers who switch between Indonesian and English. Consequently, YouTube has become an effective tool for language learning, making English more accessible and engaging for Indonesian audiences. This study aims to analyze the types, functions and factors of code-switching used on the Korean YouTube channel Reomit. The research method involves descriptive qualitative analysis, with data collection centered on five videos from the Korea Reomit YouTube channel, focusing on themes related to meats, soupy foods, and snacks. The analysis reveals that the types of code-switching present on the Korea Reomit channel include inter-sentential, intra-sentential, and tag switching. The functions of code-switching identified in the study include discussing specific topics, emphasizing points, interjections, repetition for clarification, intention for clarification, and expressing group identity. The factors influencing code-switching are identified as participant, topic, status, and solidarity.